Evaluasi Kinerja Petugas Registrasi Gampong dalam Pengurusan Akta Kelahiran dan Akta Kematian - Rahma Dewi; Ikhsan Ikhsan; Zuhrizal Fadhly (Spirit Publik: Jurnal Administrasi Publik, 2023)
The Gampong Registration Officer (PRG) is a person assigned by the village head to take carenof all population administration matters relating to the administration of birth certificates and community death certificates in the village. This activity is a form of state presence in protecting and giving recognition to the personal status and legal status of every population administration affair and other important matters experienced by Indonesian citizens. birth and death certificates in Aceh Barat District. Performance evaluation is very important in assessing the performance of the Gampong Registration Officer (PRG) for the benefit of the community. Qualitative method with descriptive approach is the method used in this research. The location of this research was conducted in West Aceh Regency. Data was collected through observation, interviews, and supporting documentation. The informants interviewed in this study were selected using non-probability sampling or the researcher determined the informants themselves with the aim of digging up information related to the research problem that had been determined by the researcher. The results showed that the performance of the Gampong Registration Officer (PRG) was good, as evidenced by the resulting increase, but this was not maximized because the establishment of Gampong Registration (PRG) was still relatively new in several villages. In addition, there are Gampong Registrations (PRGs) that have not been actively working because they have just been appointed (in SK-kan) and PRGs who have their respective activities.